2019
DOI: 10.1016/j.ijheatmasstransfer.2019.118536
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solutions for the isobaric evaporation of pure cryogens in storage tanks

Abstract: New analytical solutions have been derived for the isobaric evaporation of a pure liquid cryogen. In particular, expressions have been provided for the liquid volume, evaporation rate, Boil-off-Gas (BOG) rate, vapour temperature and vapour to liquid heat transfer rate as a function of time. Both equilibrium and non-equilibrium scenarios have been considered. In the former, the vapour and liquid cryogen are assumed to be in thermal equilibrium, while in the latter the vapour is treated as superheated with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Static evaporation characteristics in cryogenic vessels have been studied using theoretical, CFD, and experimental methods. In theoretical studies, predictions of LNG composition and BOG rate were studied based on equilibrium [5][6][7][8] and non-equilibrium [9][10][11] thermodynamics. In CFD studies, temperature distributions, heat transfer, and evaporation mechanics have been investigated [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Static evaporation characteristics in cryogenic vessels have been studied using theoretical, CFD, and experimental methods. In theoretical studies, predictions of LNG composition and BOG rate were studied based on equilibrium [5][6][7][8] and non-equilibrium [9][10][11] thermodynamics. In CFD studies, temperature distributions, heat transfer, and evaporation mechanics have been investigated [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The measured results showed that fluid thermal stratification is highly related to the thermal aspect ratio. Huerta and Vesovic 28,29 developed an analytical method to evaluate the evaporation rate of pure cryogen. The results showed that the initial liquid filling has obvious effects on the boil-off rate of pure cryogen.…”
mentioning
confidence: 99%